2006
DOI: 10.1002/cbdv.200690067
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and New Tetralone Derivatives fromBerchemia floribunda (Wall.)Brongn.

Abstract: Two new a-tetralone ( ¼ 3,4-dihydronaphthalen-1(2H)-one) derivatives, berchemiaside A and B (1 and 2, resp.), and one new flavonoid, quercetin-3-O-(2-acetyl-a-l-arabinofuranoside (3), together with ten known flavonoids compounds, eriodictyol (4), aromadendrin (5), trans-dihydroquercetin (6), cisdihydroquercetin (7), kaempferol (8), kaempferol-3-O-a-l-arabinofuranoside (9), quercetin (10), quercetin-3-O-a-l-arabinofuranoside or avicularin (11), quercetin 3'-methyl ether, 3-O-a-l-arabinofuranoside (12), and maes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…The traditional Chinese medicine (TCM) -derived drugs cephalotaxine, homoharringtonine, berberine, and cantharidin were purchased from Sigma-Aldrich and artesunate from Saokim. The other natural products were isolated from their medicinal plants of origin as described (10,11).…”
Section: Patients and Tumorsmentioning
confidence: 99%
“…The traditional Chinese medicine (TCM) -derived drugs cephalotaxine, homoharringtonine, berberine, and cantharidin were purchased from Sigma-Aldrich and artesunate from Saokim. The other natural products were isolated from their medicinal plants of origin as described (10,11).…”
Section: Patients and Tumorsmentioning
confidence: 99%
“…dol, berberine, cantharidin, cephalotaxine, curcumin, homoharringtonine, luteolin, isoscopoletin, scopoletin and others [7], [8], [9], [10], [11], [12], [13], [14], [15]. Furthermore, several novel bioactive compounds were described and analyzed in the course of our investigations, i. e., tetracentronsine A, tetracentronside A, B and C, the two novel a-tetralone derivatives berchemiaside A and B as well as the novel flavonoid quercetin-3-O-(2-acetyl-a-L-arabinofuranoside) [16], [17].…”
mentioning
confidence: 99%
“…We found that the extract of T. sinense showed significant cytotoxicity to human leukaemia cells in vitro. Recently, we reported the cytotoxic components from Berchemia floribunda [3]. As a part of our ongoing search for new biologically active compounds, we were interested in T. sinense.…”
mentioning
confidence: 99%
“…The HMBC spectrum showed the (E)-propenyl group located at C(5), which was confirmed by the correlations at d 6.44 (HÀC(8)) with 7.34 (HÀC(4)), and 6.11 (HÀC(9)) with 6.87 (HÀC(6)) in its ROESY. The relative configuration of HÀC(2) and HÀC(3) was trans as judged from the ROE correlations between HÀC(2) and MeÀC (3), and between HÀC(3) and HÀC(2',6') ( Figure). This was also confirmed by the coupling constant J(2,3) ¼ 7 Hz [4].…”
mentioning
confidence: 99%